Business process reengineering (bpr) - The latest management fad? (a concept paper) / Tang Meng Keang - Tang, Meng Keang (2004)
Managers were reported frequently introducing management fad to improve organizational effectiveness. Some managers looked at the management fad as the savior for their problematic organizations while some need it for survival, in order to battle the fierce competition it the industry. Many were reported got their hand burned by the innovativeness that they brought into their organizations. This paper however would not look at all the management fads but in fact would narrow down the scope to study one of the latest management fad - Business Process Reengineering (BPR) to explore its critical success factors, from some real organizations’ experiences and literature reviews’ perspectives. Three big cases were being discussed, namely Inland Revenue Authority of Singapore (IRAS), American National Bank of Florida (ANBF), and Blue Shield of California (BSC). All of them had been going through a difficult and successful BPR process. Their critical success factors were mainly relied on the support that they got from their own people It was not easy but there was a way to get it done through their experiences. Besides, two other critical success factors that being touched on were the role of Information Technology (IT) and team-based organizational structure These three critical success factors would be further discussed by looking at the latest research findings of the literature reviews. There might be some other critical success factors that proved to be useful but due to the length and time constraints, this paper would only discussed these three critical success factors, namely people, IT, and organizational structure.